An Antimicrobial Peptide-Loaded Chitosan/Polyethylene Oxide Nanofibrous Membrane Fabricated by Electrospinning Technology - Yu, Ling; Dou, Shubin; Ma, Jinghan; Gong, Qiang; Zhang, Mogen; Zhang, Xiquan; Li, Min; Zhang, Weifen (Frontiers in Materials, 2021)
Antimicrobial peptides (AMPs) are a new class of promising antibacterial agents. We prepared electrospinning chitosan (CS)-polyethylene oxide (PEO) nanofiber membranes containing different concentrations of an antibacterial peptide NP10. The average diameter of nanofibers increased with the total concentration of NP10. The FTIR shows that all the peaks of CS -PEO nanofiber membranes with different concentrations of NP10 were almost the same as those of pure CS -PEO nanofiber membranes，and only the peak intensity changes. Adding NP10 can improve the thermal stability of CS-PEO nanofiber membranes. In the in vitro release experiment, NP10 was released from the CS-PEO-0.5%NP10 nanofiber membrane in a burst first and then slowly and continuously. Simultaneously, the CS-PEO-NP10 nanofiber membrane had good antibacterial activity against E. coli and S. aureus and good biocompatibility. In animal wound healing experiments, CS-PEO-0.5%NP10 nanofiber membrane had advantages over gauze and CS-PEO nanofiber membrane in wound healing. These properties may provide a choice for the clinical application of AMPs and treatment of wound infections.